Intraperitoneal Administration of S100A8 Ameliorates Experimental Acute Colitis in Rats - Kano Matsuo; Masaki Ikemoto; Kohki Okada (Biology)
S100A8 is a protein that is abundant in neutrophils and macrophages (MΦ), but its role in inflammation remains unclear. This study aimed to assess the immunological role(s) of S100A8 in acute intestinal inflammation in rats and its role in MΦ. Rat recombinant S100A8 (rr-S100A8, 1.0 mg/kg) was intraperitoneally administered daily to rats with 3% dextran sulfate sodium (DSS) (DSS + A8 group)-induced experimental acute colitis. The histological severity score (6.50 ± 0.51, p = 0.038) in the DSS + A8 group rats remained lower than that (9.75 ± 1.48) of the rats without S100A8 (DSS group) administration. The tumor necrosis factor-alpha (TNF-α) production in the colon tissues of the rats in the DSS + A8 group (4.76 ± 0.90 pg/mL/g, p = 0.042) was significantly suppressed, compared with that of the DSS group (10.45 ± 2.04 pg/mL/g). To stimulate rat peritoneal MΦ, rr-S100A8, the anti-rat S100A8 antibody, and a lipopolysaccharide (LPS) were used in the in vitro experiments. In the MΦ stimulated with rr-S100A8 for 2 h, the mRNA level of intracellular S100A8 (47.41 ± 24.44, p = 0.002) increased in an autocrine manner, whereas that of S100A9 (0.24 ± 0.43, p = 0.782) was not significant. The TNF-α mRNA level in the MΦ treated with LPS and the anti-rat S100A8 antibody significantly increased (102.26 ± 18.60, p = 0.001) compared to that with LPS alone (16.9 ± 8.56). These results indicate that S100A8 can serve as an anti-inflammatory protein in acute inflammation by negatively regulating S100A9 and TNF-α production through inflammatory signaling pathways in MΦ.